Indonesia’s Foreign Policy in Promoting a Moderate Islamic Identity after the Reform - Naim, Sidrotun; Mokodenseho, Sabil (JURNAL AT-TURAS, 2023)
This study aims to analyze the factors that have led to changes in Indonesia’s foreign policy, which initially avoided the emergence of a moderate Islamic identity but currently makes efforts to promote it. The research is essential as it sheds light on Indonesia’s foreign policy practices, which have historically refrained from emphasizing an Islamic identity, despite the country’s predominantly Muslim population. Furthermore, this research holds significant importance as it addresses the negative perceptions of Islam, which have often associated it with terrorism, intolerance, and opposition to peace, particularly from Western perspectives. In this study, the researchers utilized a qualitative descriptive method employing content analysis techniques to analyze the collected data. The examination of Indonesia’s foreign policy reveals its aspirations to pursue international interests by actively engaging in maintaining global peace and prioritizing a moderate Islamic identity. This study concludes that a moderate Islamic identity, as a facet of identity, is not inherently problematic or conflict-ridden; rather, it has the potential to bridge the divide between the West and Islam. Moreover, Western countries express their desire to cultivate networks of moderate Islam and view Indonesia as a competent partner in countering global terrorist networks. This cooperation stems from the shared principles of democracy and respect for human rights upheld by both the West and Indonesia.